KRIMINALISASI KUMPUL KEBO (SAMEN LEVEN) MENURUT RANCANGAN KITAB UNDANG-UNDANG HUKUM PIDANA - Irwansyah '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Cohabiting (samen leven), which is a real phenomenon in the life of society, Deeds lived together between men and women without bound by a rope legitimate marriage becomes an ordinary thing to do in the community, the presumptions among these was a part of modern life. Those who have done cohabiting occur due to funding constraints, not mendafatkan blessing of the parents or to the satisfaction of baitiniah alone. However, cohabiting seen most of Indonesian people as a disgraceful act and included a crime against decency. But in the Code of Criminal Penal Code in force today, coming from Wetboek Van Strafrechtvoor Netherlands Indies (WvS) days of the Dutch East Indies, cohabiting is not expressed as acts that can be punished. But cohabiting by most of the majority of customary law is alive and thriving in Indonesia is regarded as a crime of morality, therefore designers laws incorporate customary law (gewoonrecht) into the draft Criminal Code contained in article 485 stating that everyone who performs live together as husband and wife outside a valid marriage, shall be punished by a maximum imprisonment of 1 (one) year or a fine of category II, in respect of dimasukanya cohabiting into the Criminal Code draft, it appears some opinions that the pros and cons and that would lead to horizontal conflict. The purpose of this thesis, namely: first, the underlying reasons criminalizing cohabitation as an offense in the draft Book of Law Criminal Law, second, setting cohabiting acts as an offense under applicable positive law in Indonesia. This type of research can be classified into types of research Normative that this study in terms of the Normative were reviewing legislation prundang law, in this study, the data source is in use, the primary data, secondary data, the data tertiary data collection techniques in this study to examine legislation OF, draft legislation and studies into the library. From the research there are two main things that can be inferred setting cohabiting in the Draft Penal Code Book as one form of criminalization based on a variety of reasons, among other reasons derived from socio philosophical foundation of the socio-cultural and national legal systems derived from results of studies and excavations national values derived from Pancasila and values in society (religious values and cultural values (traditional)); violating the values of decency (national agreement) contained in Pancasila containing values based on the nationality berkehidupan Almighty God (religious moral values); and the reason comes from foundation research and comparative studies bahwasannya cohabiting has been set and be made a criminal offense in the Criminal Code foreign countries. The foundation provides a variety of conclusions that lead to the need for the criminalization of cohabiting into a positive law. Keywords: Sanctions - Bill - Cohabiting